The Role of IT Mindfulness and Task Technology Fit to Understanding the Continuous Use of Fintech by MSMEs - Soemarno Hidayatullah.S; Asmirawati; Muhammad Niswar Adhytama (Indonesian Journal of Taxation and Accounting, 2026)
Purpose - This study examines the determinants of continuance intention to use Financial Technology (Fintech) among Micro, Small, and Medium Enterprises (MSMEs) in Indonesia by integrating the Expectation-Confirmation Model (ECM), Task-Technology Fit (TTF), and IT mindfulness. Methods - A quantitative cross-sectional survey design was employed, involving 430 Indonesian MSMEs that had experience using Fintech services, including peer-to-peer lending, crowdfunding, and digital payment systems. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Findings - The results indicate that user satisfaction, perceived usefulness, IT mindfulness, and task-technology fit significantly influence continuance intention to use Fintech. In addition, confirmation significantly affects perceived usefulness, user satisfaction, and IT mindfulness, while task-technology fit positively influences confirmation, perceived usefulness, and satisfaction. These findings suggest that continuance intention is shaped not only by post-adoption cognitive evaluations, as proposed in ECM, but also by users’ mindful engagement with technology and the alignment between Fintech features and MSME operational tasks. Research Implications - The findings also provide practical implications for Fintech providers in designing services that better align with MSMEs’ business processes and usage requirements. Originality - This study contributes to the Fintech continuance literature by empirically extending ECM through the integration of IT mindfulness and TTF in the MSME context.